Simultaneous HESS and Chandra observations of Sagitarius A during an X-ray flare - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
The rapidly varying ( 10 min timescale) non-thermal X-ray emission observed from Sgr A implies that particle acceleration is occuring close to the event horizon of the supermassive black hole. The TeV γ-ray source HESSJ1745-290 is coincident with Sgr A* and may be closely related to its X-ray emission. Simultaneous X-ray and TeV observations are required to elucidate the relationship between these objects. We report on joint HESS/Chandra observations performed in July 2005, during which an X-ray flare was detected. Despite a factor of ≈9 increase in the X-ray flux of Sgr A*, no evidence is found for an increase in the TeV γ-ray flux from this region. We find that an increase in the γ-ray flux of a factor of 2 or greater can be excluded at a confidence level of 99%. This finding disfavours scenarios in which the keV and TeV emission are associated with the same population of accelerated particles and in which the bulk of the γ-ray emission is produced within ∼ cm (∼100 Rs) of the supermassive black hole. © 2008 ESO.
Keywords: Gamma rays: observations; X-rays: individuals: Sgr A